Dynamics of Entanglement and Measurement-Induced Disturbance for a Hybrid Qubit-Qutrit System Interacting with a Spin-Chain Environment: A Mean Field Approach. (January 2017) - Jafarpour, M.; Hasanvand, F Kazemi; Afshar, D.
Abstract: We use the mean field method to study the dynamics of thermal entanglement and also the measurement-induced disturbance for a mixed qutrit-qubit system coupled to an environment, comprised of an Ising spin-chain with long range interactions, embedded in a transverse magnetic field. It is revealed that both quantities die down in long enough time and the fade out time is a decreasing function of temperature; however, the environmental magnetic field holds back the decoherence, and increases the fade out time; thus, providing a means to control and postpone the decoherence process. Moreover, it is observed that the discrepancy between the interaction strength of the qubit and the qutrit with the environment, substantially affects the decoherence behavior of the system.